Geochemical Characteristics of Helium in Natural Gas From the Daniudi Gas Field, Ordos Basin, Central China - Liu, Quanyou; Wu, Xiaoqi; Jia, Huichong; Ni, Chunhua; Zhu, Jianhui; Miao, Jiujun; Zhu, Dongya; Meng, Qingqiang; Peng, Weilong; Xu, Huiyuan (Frontiers in Earth Science, 2022)
Helium-bearing gas is accumulated in the Lower Ordovician, Upper Carboniferous, and Lower Permian reservoirs of the Daniudi gas field in Ordos Basin, and the helium concentrations and isotopic compositions are investigated in order to reveal the abundance and origin of helium. Geochemical characteristics indicate that the natural gas from the Daniudi gas field has helium concentrations of 0.0271–0.1273%, with R/Ra ratios of 0.007–0.072. The 4He/20Ne ratios range from 848 to 17,000, which are substantially higher than the ratio of air or air saturated water. The proved helium reserves of the Daniudi gas field exceed 100 × 106 m3, suggesting an extra-large helium gas field. Helium in the field is of crustal origin and derived from the radioactive decay of U and Th in the rocks and minerals, with no significant contribution by atmospheric or mantle-derived helium. The natural gas in the Daniudi gas field displays the characteristics of typical crustal helium, which is consistent with the gases from cratonic basins (Ordos, Sichuan, and Tarim) in China, whereas the gases from rift basins (Songliao, Bohai Bay, and Subei) have experienced a significant addition of mantle-derived helium.